2003
DOI: 10.1111/j.1365-2567.2003.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of C5a receptor expression and function on human monocyte derived dendritic cells by prostaglandin E2

Abstract: Summary The expression of the C5a‐receptor (C5aR) on dendritic cells, its regulation and function have not been well established thus far. We show that the C5aR is expressed on human monocyte‐derived dendritic cells (DC) and can be down‐regulated by maturation stimuli such as tumour necrosis factor‐α (TNF‐α), lipopolysaccharide (LPS) or CD40L and by the T helper 1‐cytokine interferon‐γ (INF‐γ). Prostaglandin E2 (PGE2), a proinflammatory mediator supporting dendritic cell activation and necessary for adequate D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
1
19
0
1
Order By: Relevance
“…It has been shown that C3a or C5a stimulation induces F-actin polymerisation in monocytes derived DCs and plamacytoid DCs, and up-regulates the surface expression of CD54, CD83 and CD86 and gene expression of complement receptors (C3aR, C5aR) and complement components (C3, FB) in monocytes derived DCs (Weinmann et al 2003;Gutzmer et al 2006Gutzmer et al , 2004Li et al 2011). However, the functional significance of these observations, in terms of participating in T cell regulation is not well defined.…”
Section: Acting On Dendritic Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been shown that C3a or C5a stimulation induces F-actin polymerisation in monocytes derived DCs and plamacytoid DCs, and up-regulates the surface expression of CD54, CD83 and CD86 and gene expression of complement receptors (C3aR, C5aR) and complement components (C3, FB) in monocytes derived DCs (Weinmann et al 2003;Gutzmer et al 2006Gutzmer et al , 2004Li et al 2011). However, the functional significance of these observations, in terms of participating in T cell regulation is not well defined.…”
Section: Acting On Dendritic Cellsmentioning
confidence: 95%
“…Recent research has also shown that murine DCs and several human DC subsets [i.e. monocyte derived, dermal, Langerhans, myeloid, plamacytoid] also express C3aR or/and C5aR and the expression can be regulated by different stimuli such as pathogen, inflammatory mediators and complement products Li et al 2011;Gutzmer et al 2004;Weinmann et al 2003;Gutzmer et al 2006). GeneChip analysis of human tissue samples has revealed that C5aR are expressed most abundantly in granulocytes (e.g.…”
Section: Experimental Modelmentioning
confidence: 98%
“…It has been shown that C3a [10,14] and C5a [11,15] are able to attract immature DCs to the peritoneal cavity of severe combined immunodefi ciency (SCID) mice and that iC3b-covered apoptotic cells are more effi ciently engulfed by immature DCs [16,17], resulting in reduced expression of costimulatory molecules and impaired DC maturation. Castellano et al [6] of complement gene expression in DCs seems to be both gene and stimuli-specifi c.…”
Section: Complement Mrna Expressionmentioning
confidence: 99%
“…[11][12][13] Furthermore, it has been shown that C5aR is expressed on DCs and T cells. 11,14 -16 The expression is upregulated in DCs in response to pathogenic or inflammatory stimuli (e.g., LPS and prostaglandin E 2 ) 14,15 and in T cells when encountering APCs. 11,12 These findings suggest that C5aR-ligand interactions can upregulate antigen-specific T cell responses by modulating the activation of APCs and T cells.…”
mentioning
confidence: 99%